Negative impact of coronavirus on interventional cardiology fellows' training: Let's limit collateral damage of the pandemic. Issue 2 (15th February 2021) - Tarantini, Giuseppe; Nai Fovino, Luca
Key Points: Coronavirus disease pandemic has caused a dramatic reduction of elective and urgent interventional cardiology procedures, with a negative impact on training of interventional cardiology fellows. This study showed that 95% of interventional cardiology fellows during the first wave of the COVID‐19 pandemic believe that their training would be moderately or severely impacted by the health crisis. Interventional cardiology programs need to reorganize in order to ensure safe pathways for both urgent and elective cases, primarily for patients' care but also to grant an adequate caseload for trainees.